PROFITABILITY, LIQUIDITY, AND ASSETS: HOW FIRM SIZE SHAPES CAPITAL STRUCTURE IN INDONESIAN MANUFACTURING - Raharjanti, Rani; Fitriani, Hervina; Murtini, Sri (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2024)
The current research seeks to assess the impact of profitability, liquidity, and asset structure on capital structure, with company size serving as a moderating variable, in manufacturing firms listed on the Indonesia Stock Exchange from 2019 to 2023. The research sample comprised 66 companies chosen using purposive sampling. The utilized data source is secondary data. This research employs multiple linear regression analysis conducted using SPSS. The research findings demonstrate that profitability and liquidity positively influence capital structure, but asset structure negatively impacts capital structure. The company's size can mitigate the impact of profitability, liquidity, and asset composition on capital structure.